Microsurgical anatomy and pathoanatomy of the outer arachnoid membranes in the cerebellopontine angle: cadaveric and intraoperative observations - Kurucz, Peter; Ganslandt, Oliver; Buchfelder, Michael; Barany, Laszlo (Acta Neurochirurgica, 2023)
Purpose: The cerebellopontine angle (CPA) is a frequent region of skull base pathologies and therefore a target for neurosurgical operations. The outer arachnoid is the key structure to approach the here located lesions. The goal of our study was to describe the microsurgical anatomy of the outer arachnoid of the CPA and its pathoanatomy in case of space-occupying lesions. Methods: Our examinations were performed on 35 fresh human cadaveric specimens. Macroscopic dissections and microsurgical and endoscopic examinations were performed. Retrospective analysis of the video documentations of 35 CPA operations was performed to describe the pathoanatomical behavior of the outer arachnoid. Results: The outer arachnoid cover is loosely attached to the inner surface of the dura of the CPA. At the petrosal surface of the cerebellum the pia mater is strongly adhered to the outer arachnoid. At the level of the dural penetration of the cranial nerves, the outer arachnoid forms sheath-like structures around the nerves. In the midline, the outer arachnoid became detached from the pial surface and forms the base of the posterior fossa cisterns. In pathological cases, the outer arachnoid became displaced. The way of displacement depends on the origin of the lesion. The most characteristic patterns of changes of the outer arachnoid were described in case of meningiomas, vestibular schwannomas, and epidermoid cysts of the CPA. Conclusion: The knowledge of the anatomy of the outer arachnoid of the cerebellopontine region is essential to safely perform microsurgical approaches as well as of dissections during resection of pathological lesions.
CRIS-Team Scopus Importer:2023-05-19
Keywords: Arachnoid; Cerebellopontine angle; Epidermoid cyst; Meningioma; Surgical anatomy; Vestibular schwannoma